Impact of SIEM on Compliance: Achieving Security and Adherence Simultaneously - Jangampeta, ShivaDutt; Khambam, Sai Krishna Reddy (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
Security Information and Event Management (SIEM) solutions are broadly used as important tools to identify, prevent, and respond to cyber security incidents. Recently, SIEM systems have immensely advanced to become extensive solutions that provide a broad view of IT infrastructures, help IT teams spot cyber risks, and devise proactive mitigation strategies aimed at minimizing time and expenditure for incident response. Besides, SIEM addresses a vast range of regulatory requirements, like state and international regulations with which organizations must comply together with industry-specific policies and standards. As such, this review paper explains how SIEM helps businesses meet regulatory requirements and achieve compliance with industry best practices.